Egresso do curso de administração do Instituto de Natureza e Cultura, no Alto Solimões: desafios e possibilidades para empreender em Benjamin Constant-Amazonas - Marinho, Natalia Barbosa (Brasil, 2023)
Entrepreneurship is present in all socioeconomic segments, including the university environment, in which it is possible to prepare students for the job market, especially if they have the desire to be an entrepreneur. This makes the university the central base for the acquisition of knowledge about entrepreneurship, so that the student can undertake successfully when he or she becomes an alumnus of higher education courses in the business area. The present work had the general objective of investigating in which socioeconomic activities the egresses of the Administration course of the Institute of Nature and Culture, undertake in the municipality of Benjamin Constant, in Alto Solimões-Amazonas. The methodological procedures that guided the research involved a qualitative and descriptive approach. Data was obtained through a documental survey and field research, which was conducted via interviews with eight graduates from the Administration course in the municipality of Benjamin ConstantAM. As a result of the research, it was found that, in general, the majority are women, single, have been in business between two and three years and have already taken professional qualification courses in the area of activity, and two have already taken post-graduate courses, as a continuation of their academic training. It is concluded that entrepreneurship has been occupying a significant role in the most diverse economic segments, a fact that makes this subject relevant in the university environment, signaling the need for greater institutional attention as to the possibilities of training for the awakening of the entrepreneurial spirit of the graduates, who should be continuously monitored by the institution that trains them, in order to improve the relationship between theory and practice in the period of their academic training.